Rāingān kānsưksā khrōngkān tittām pramœ̄nphon kānphatthanā khrōngkān nưng tambon nưng phalittaphan (Samnakngān Khana Kammakān Phatthanākān Sētthakit læ Sangkhom hǣng Chāt, 2014)
On rural economic conditions in Thailand after implementation of "one tambon one product" project.